2016
DOI: 10.1016/j.ijscr.2016.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Urological injuries associated with pelvic fractures: A case report of a detached bone segment inside the bladder

Abstract: HighlightsA 45-year-old pedestrian male was hit by a car.Gross hematuria was evident upon inserting Foley’s catheter.CT revealed multiple stable pelvic fractures.CT cystogram showed intraperitoneal and extraperitoneal extravasation of contrast.A detached pubic bone fragment was found inside the urinary bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…There is also a possibility of urinary bladder injury in patients with sacral injury. Gross hematuria is a hallmark sign of bladder injury in the presence of pelvic fracture in 16-27% of patients (Alfayez et al 2016). However, microscopic hematuria in the absence of overt signs of lower urinary tract injury is probably not indicative of bladder rupture (Figler et al 2012), just as in this case, where there was no gross hematuria but microscopic examination of the urine did detect the presence of red blood cells.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…There is also a possibility of urinary bladder injury in patients with sacral injury. Gross hematuria is a hallmark sign of bladder injury in the presence of pelvic fracture in 16-27% of patients (Alfayez et al 2016). However, microscopic hematuria in the absence of overt signs of lower urinary tract injury is probably not indicative of bladder rupture (Figler et al 2012), just as in this case, where there was no gross hematuria but microscopic examination of the urine did detect the presence of red blood cells.…”
Section: Discussionmentioning
confidence: 65%
“…A systematic method of approaching a trauma patient in Advanced Trauma Life Support (ATLS) protocol was taught to emergency doctors so that any lifethreatening injury is not missed out and may be promptly attended if any such was found. Sacral fracture, although not life-threatening, could have serious complications which are neurological injury (Beckmann & Chinapuvvula 2017) and urological injury with concurrent pelvic fracture (Alfayez et al 2016). However, due to its rarity, it is frequently overlooked and hence, not properly treated (Rodrigues-Pinto et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…14,20 Pelvic fracture is a significant risk factor for bladder injury with 90% of bladder injuries associated with pelvic fracture. 21 Given the high risk of concomitant injury, first responders, trauma providers, and physicians are taught to have a high index of suspicion for bladder injury in patients with a pelvic fracture. 14,21 Interestingly, we found that a BAC above the legal limit of 0.08 g/dL was more predictive of bladder injury requiring surgical repair than occurrence of pelvic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Associated concurrent GU injuries range between 6 and 15% of the cases [ 9 , 11 13 ]. Although the bladder and urethra are internalized, sterile structures susceptible to injury from pelvic fractures.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%